ANALYSIS OF STUDENTS' LEARNING DIFFICULTIES IN ENGLISH SUBJECTS USING KURIKULUM MERDEKA IN ELEMENTARY SCHOOLS - Rosyadi, Wildan Fakhri (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2024)
Learning English in elementary schools often still experiences various obstacles. For this reason, the author conducted this research to find out students' learning difficulties as well as solutions that can be taken in learning English at the elementary school level with the ikurikulum merdeka as the curriculum. The method used in this research is a literature review approach in the form of a description of theories and findings obtained from various sources which are used as study material. This student's learning difficulties are characterized by not achieving the learning objectives that have been set. The causes of these difficulties include internal and external factors. Then, from the analysis carried out, researchers obtained solutions that could be taken to overcome these problems. Considering the importance of knowledge of English as an international language in the modern technological era like today.